2018
DOI: 10.1192/bjp.2017.34
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of staff training in positive behaviour support to reduce challenging behaviour in adults with intellectual disability: cluster randomised controlled trial

Abstract: BackgroundStaff training in positive behaviour support (PBS) is a widespread treatment approach for challenging behaviour in adults with intellectual disability.AimsTo evaluate whether such training is clinically effective in reducing challenging behaviour during routine care (trial registration: NCT01680276).MethodWe carried out a multicentre, cluster randomised controlled trial involving 23 community intellectual disability services in England, randomly allocated to manual-assisted staff training in PBS (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 34 publications
4
77
4
1
Order By: Relevance
“…The present analysis using data from a cluster randomised trial of staff training in delivering PBS suggests that the intervention did not reduce challenging behaviour in ASD+ participants. These findings are in keeping with the main trial findings, which showed no effect of staff training in PBS on reducing challenging behaviour [40]. In line with other studies [48][49][50][51][52], ASD+ participants displayed a high level of challenging behaviour.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The present analysis using data from a cluster randomised trial of staff training in delivering PBS suggests that the intervention did not reduce challenging behaviour in ASD+ participants. These findings are in keeping with the main trial findings, which showed no effect of staff training in PBS on reducing challenging behaviour [40]. In line with other studies [48][49][50][51][52], ASD+ participants displayed a high level of challenging behaviour.…”
Section: Discussionsupporting
confidence: 92%
“…The current study aims to investigate whether staff training in PBS delivery is clinically and cost effective compared to treatment as usual in adults with ASD+, in a trial described previously [40]. In summary, this was a multicentre, two-arm cluster randomised controlled trial in which 246 adults with ID (with and without ASD) were recruited from 23 community intellectual disability services across England.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations